The Effect of Coating as Antifungi of Harumanis Mango's Post Harvest Losses - Winda Amilia; Andrew Setiawan Rusdianto; Arma Dwi Novemi (Newinera Publisher, 2020)
The amount of mango production in Indonesia is quite high, but the quality of postharvest mangoes is still quite low. The quality of the fruit will decline due to contamination; one of the contaminants is fungi. The way to reduce the damage of postharvest products is by coating applications. The purpose of this study was to study the physical, chemical and antifungal activities of harumanis mangoes’s quality which had been given coating during storage that could cause postharvest losses of harumanis mangoes. There are 3 treatments, each of them are respectively the provision of corn based coating 6% tobacco extract, 8% tobacco extract and 10% tobacco extract. The physical and chemical properties of the antifungal coating of tobacco extract made from corn coating for post-harvest damage on harumanis mangoes were obtained by weight loss, texture, colour, respiration rate, vitamin C and total dissolved solid. Preventing coating can prevent damage after harvest and protect the harumanis mango; therefore the quality of the mangoes can be maintained. The best results from the priority with the largest diameter inhibition zone were given corn starch 10% tobacco extract. Then the higher the concentration of extract used, the greater the diameter of the inhibition zone obtained. Based on all the tests performed (physical, chemical, and antifungal) the best treatment from the treatment was obtained that consisted of mangoes with antifungal layers of corn starch 10% tobacco extract. Because the P3 obtained the best results in maintaining physical, chemical content and fungi for 15 days.